PENERAPAN PENDEKATAN MATEMATIKA REALISTIK INDONESIA ( PMRI ) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA KELAS II SD NEGERI 003 SUNGAI GUNTUNG KECAMATAN RENGAT KABUPATEN INDRAGIRI HULU - Marlina, Yeni; Alim, Jesi Alexander; Alpusari, Mahmud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research is motivated by the learning process has been unsatisfied, because teachers not use appropriate learning model that makes the lack of student interest in paying attention. This research purpose to improve learning to result math grade II through the application learning models realistic mathematics education ( PMR ) in SD Negeri Sungai Guntung Tengah. The implementation done in two cycles, each cycle consisting of two meetings. The cycle I was conducted on 18 March – 25 March 2015 and cycle II was conducted on 27 March – 8 April 2015. The first meeting teacher activity precentage 72,22%, first meeting to second meeting cycle teacher precentage increased by 2,78% to 75%, and the thirth meeting 5,56% to 88,89% and fourth meeting increased by 5,55% to be 94,44% with the execellent category. The first meeting student activity is 66,67%, first meeting to second meeting student increased 5,55% to 72,22%, thirth meeting increased 13,89% to 86,11%, fourth meeting increased 5,565 to 91,67% with the execellent category. From the analysis of the result showed that the student’s learning result math facts on the basis of average scores 67,69% increased by 69,56% for cycle I with percentage increased by 1,87% and for cycle II average increased by 70,68% with percentage increased by 2,39%. The percentage of the number of students in the classical mastery of the score 52,17% for the test cycle I increased by 13,05% until percentage by 65,22%. And for the test cycle II increased by 21,73% until by 86,95%. The result this research concluded that the application of Indonesian Realistic Mathematics Education ( PMRI ) can be increased the learning math grade II result in SD Negeri 003 Sungai Guntung Tengah of the years 2014/2015.Key Words : Model Indonesian Realistic Mathematics Education ( PMRI ), Mathematics Result Learning.